2014
DOI: 10.1007/s10548-014-0387-1
|View full text |Cite
|
Sign up to set email alerts
|

Narcoleptic Patients Show Fragmented EEG-Microstructure During Early NREM Sleep

Abstract: Narcolepsy is a chronic disorder of the sleep-wake cycle with pathological shifts between sleep stages. These abrupt shifts are induced by a sleep-regulating flip-flop mechanism which is destabilized in narcolepsy without obvious alterations in EEG oscillations. Here, we focus on the question whether the pathology of narcolepsy is reflected in EEG microstate patterns. 30 channel awake and NREM sleep EEGs of 12 narcoleptic patients and 32 healthy subjects were analyzed. Fitting back the dominant amplitude topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 57 publications
4
36
1
1
Order By: Relevance
“…Our group followed this approach in all our previous publications on EEG microstates (Brodbeck et al, 2012; Kuhn et al, 2015; von Wegner et al, 2017). To find local maxima of the GFP time series, we first compute the discrete time derivative δ i = σ i +1 − σ i , and then identify local GFP maxima as the set of time points I max where the sign of δ i crosses from positive to negative values, i.e.,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group followed this approach in all our previous publications on EEG microstates (Brodbeck et al, 2012; Kuhn et al, 2015; von Wegner et al, 2017). To find local maxima of the GFP time series, we first compute the discrete time derivative δ i = σ i +1 − σ i , and then identify local GFP maxima as the set of time points I max where the sign of δ i crosses from positive to negative values, i.e.,…”
Section: Methodsmentioning
confidence: 99%
“…Among these, the reader can find resting-state experiments (Britz et al, 2010; Musso et al, 2010; Van de Ville et al, 2010; Brodbeck et al, 2012), different task-related conditions (Dimitriadis et al, 2013, 2015; Milz et al, 2015; Dimitriadis and Salis, 2017) and sleep (Brodbeck et al, 2012). Clinical conditions include schizophrenia (Koenig et al, 1999), Alzheimer's disease (Nishida et al, 2013), and narcolepsy (Kuhn et al, 2015; Drissi et al, 2016). An overview of the field has recently been published in two reviews (Khanna et al, 2015; Michel and Koenig, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Resting state EEG studies typically produce four consistently observable microstates, thought to originate from the abstract thoughts that typically arise during unstructured rest [91] and whose topographies have been arbitrarily labeled A, B, C, and D ( Figure 2) [92]- [94] . These four microstates are consistently observable and can be observed even in sleep [95] . [97] Previous studies in diseased populations have all observed changes in mean duration, frequency of occurrence, ratio of total time, and transition probability in patients relative to controls, which they interpreted as underlying changes in resting state brain dynamics characteristic of the disease (See Khanna et al [96] for a more complete review of the current resting state EEG microstate literature.…”
Section: Eeg Microstatesmentioning
confidence: 75%
“…Some research in the resting state EEG defined the brain activity as 4 types of microstates [ 6 9 , 11 , 34 , 35 , 38 , 39 ], corresponding to the 4 resting state networks; Meanwhile, in task states, the number of microstates is usually unknown, and to find the optimal cluster number, researchers often use the cross validation method [ 32 , 40 ].…”
Section: Methodsmentioning
confidence: 99%